2017
DOI: 10.1002/kin.21144
|View full text |Cite
|
Sign up to set email alerts
|

Acetylation of Glycerol over Highly Stable and Active Sulfated Alumina Catalyst: Reaction Mechanism, Kinetic Modeling and Estimation of Kinetic Parameters

Abstract: The Langmuir–Hinshelwood–Hougen–Watson (LHHW) kinetic model was developed for acetylation of glycerol over highly stable and active 2 M SO42−/γ‐Al2O3 catalyst. The apparent reaction rate constants were determined by numerically solving the differential rate equations using ode23 tool in MATLAB coupled with the genetic algorithm optimization technique. The estimated rate constants were used to obtain the activation energy and pre‐exponential factor by using the Arrhenius equation. The estimated activation energ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(5 citation statements)
references
References 35 publications
0
5
0
Order By: Relevance
“…In contrast, the lower values of activation energy and higher values of rate constant for the first and second reaction favoured the faster formation of monoacetin and diacetin. The high yield of diacetin can also be attributed to the direct acetylation of glycerol in the early phases as suggested by the reaction mechanisms proposed in the literature (Pankajakshan et al, 2018).…”
Section: Discussionmentioning
confidence: 74%
See 1 more Smart Citation
“…In contrast, the lower values of activation energy and higher values of rate constant for the first and second reaction favoured the faster formation of monoacetin and diacetin. The high yield of diacetin can also be attributed to the direct acetylation of glycerol in the early phases as suggested by the reaction mechanisms proposed in the literature (Pankajakshan et al, 2018).…”
Section: Discussionmentioning
confidence: 74%
“…9) displays a linear behaviour and the activation energy values of 5.34, 16.40, and 43.57 kJ.mol -1 were calculated for the formation of monoacetin, diacetin, and triacetin, respectively. Pankajakshan et al (2018) reported the kinetic parameters for glycerol acetylation using a sulphated γ-Al2O3 catalyst. The very high activation energy for the third reaction and low value of rate constant could explain the lower yield of triacetin obtained by the authors.…”
Section: Discussionmentioning
confidence: 99%
“…In this sense, the exceptional properties of alumina-based catalysts, such as porosity, large specific surface area, chemical stability and their addressable Lewis and Brønsted acid sites for glycerol conversion, have made them of particular interest in the EG reaction [3,13,[17][18][19][20]. However, the main disadvantages of these types of solid acid catalysts for glycerol esterification are their low water tolerance, leaching of active sites and low selectivities to the acetins, which significantly restrict their performance in the reaction [5,[17][18][19][20].…”
Section: Introductionmentioning
confidence: 99%
“…In this sense, the exceptional properties of alumina-based catalysts, such as porosity, large specific surface area, chemical stability and their addressable Lewis and Brønsted acid sites for glycerol conversion, have made them of particular interest in the EG reaction [3,13,[17][18][19][20]. However, the main disadvantages of these types of solid acid catalysts for glycerol esterification are their low water tolerance, leaching of active sites and low selectivities to the acetins, which significantly restrict their performance in the reaction [5,[17][18][19][20]. Overall, strategies for acidity modulation of the catalysts that permit the control of acid strength, types of acid sites and surface acidity to minimize the problem on water deactivation and subsequently improving the selectivity of diacetin and triacetin are vastly documented [6,11,15,20].…”
Section: Introductionmentioning
confidence: 99%
“…Monoacylglycerol is a valuable food additive, while the others are fuel additives that reduce viscosity, when mixed with diesel, or improve anti-knocking properties, when mixed with gasoline. [167,168] Scheme 1.18. Catalytic glycerol esterification [169] In a one-pot glycerol esterification, at 110 o C, over guanidine derivatives, 78% selectivity to monoglycerides can be achieved, starting from (CH 3 )OCOC 11 H 23 [169] combined selectivity, without formation of undesired by-products, such as isobutylene oligomers [173].…”
Section: Glycerol Esterificationmentioning
confidence: 99%